Recycling of Spent Oyster Mushroom Substrate to Recover Additional Value - Siddhant; Singh, C.S. (Kathmandu University Journal of Science, Engineering and Technology, 2009)
After the cultivation of Pleurotus eous, possibilities of reutilization of spent mushroom substrate (SMS) was carried out in form of ingredient for the cultivation of three oyster species, viz., Pleurotus sajor-caju Strain- Malasia, Pleurotus florida Strain-P1 and Pleurotus flabellatus and as fertilizer for growing Spinacea oleracea. As an ingredient, it was mixed properly with fresh wheat straw @ 10,15 and 25 % where 25% SMS supplemented sets showed significant yield and biological efficiency of mushrooms than control. It was recorded 345 gm, 69%; 565 gm, 113% and 525 gm, 105% for Pleurotus sajor-caju Strain- Malasia, Pleurotus florida Strain-P1 and Pleurotus flabellatus respectively. For use as a fertilizer, SMS was infested in to the soil at three different proportions (1, 3 and 5%). It showed quick seed emergence and higher yield than pure soil, however, the yield was recorded significant only in 5% SMS containing sets.